2010
DOI: 10.1016/j.pain.2009.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant sensory responses are dependent on lesion severity after spinal cord contusion injury in mice

Abstract: Following spinal cord injury (SCI), individuals lose normal sensation and often develop debilitating neuropathic pain. Basic research has helped to elucidate many of the underlying mechanisms, but unanswered questions remain concerning how sensation changes after SCI and potential negative consequences of regenerative therapies. Mouse models provide an opportunity to explore these questions using genetic markers and manipulations. However, despite the increasing use of mice in pain and sensory research, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 111 publications
(160 reference statements)
4
26
0
1
Order By: Relevance
“…At the same time, pain behaviors like over-grooming and licking or biting of the hind paws characteristic of spinal cord-injured BALB/C, but not C57BL/6 mice, the strain used here (Kerr and David, 2007), were not observed in either control or L1-and/or Chase-treated animals. These observations suggest that our treatments did not lead to exaggerated abnormal changes in sensation like allodynia or hyperalgesia (Hoschouer et al, 2010).…”
Section: Resultsmentioning
confidence: 60%
“…At the same time, pain behaviors like over-grooming and licking or biting of the hind paws characteristic of spinal cord-injured BALB/C, but not C57BL/6 mice, the strain used here (Kerr and David, 2007), were not observed in either control or L1-and/or Chase-treated animals. These observations suggest that our treatments did not lead to exaggerated abnormal changes in sensation like allodynia or hyperalgesia (Hoschouer et al, 2010).…”
Section: Resultsmentioning
confidence: 60%
“…Similarly, Siddall and colleagues 22 found that more damage to the central and dorsal regions of the spinal cord was significantly related to increased allodynia in rats. A study by Hoschouer et al 23 showed that thermal sensitivity was increased in the hind paws irrespective of injury severity, and that severe spinal contusion in mice, with <2% white matter sparing within the STT area of the spinal cord, was associated with shorter latencies of response to light mechanical stimulation (i.e., mechanical allodynia). Other studies have proposed a complex relationship between these two pathways and suggest that nociceptive activity is dependent upon the convergence of afferent input from both the STT and DCML pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, autotomy occurs in the neuroma (complete peripheral nerve transection) model, where transmission of pain that would be caused by the self-directed behavior is eliminated (Minert et al, 2007). Similarly, OG in the present study occurs in areas denervated by the SCI (Hoschouer et al, 2009). If the mechanism of induction of self-directed behavior is similar between peripheral nerve models and our SCI model, we would expect the high incidence of OG to be due to a combination of repeated afferent stimulation, followed by an afferent barrage or cytokine release within the injured spinal cord as a result of the contusion injury.…”
Section: Figmentioning
confidence: 50%
“…Sensory testing on the trunk is rapid, efficient, and relevant (Hoschouer et al, 2009). However, we show here that extensive sensory testing prior to mid-thoracic contusion injury increases overgrooming, indicative of aberrant sensation.…”
Section: Figmentioning
confidence: 99%